Classroom Psychological Abuse: A Qualitative Study Involving Students, Teachers, and Parents - Ladesma, Honey Mae; Ubaub, Julius (Journal of Educational Research and Policies, 2026)
In school environments, psychological abuse by teachers is a serious but frequently disregarded problem that manifests itself in a variety of ways, including rejection, ignorance, terrorisation, isolation, corruption, and exploitation. Unlike other forms of abuse, this one can have a lasting impact on students, affecting both their general well-being and academic performance. Regretfully, students might not be aware of this kind of abuse, which makes it more difficult for them to confront and deal with its effects. In contrast to other types of abuse, this one may affect students' general well-being as well as their academic achievement in the long run. Unfortunately, it's possible that students are unaware of this type of abuse, which makes it more challenging for them to confront and address its effects. To gather data, a purposive sampling method was employed. Semi-structured interviews with students, their parents and teachers were conducted in order to examine their perceptions. Boys in Patna schools are still frequently subjected to corporal punishment. Although none of the potential participants were aware of psychological abuse, they have all at least once encountered it in their educational setting. 3 teachers from government school and 2 from private school teacher said they use it unconsciously to maintain their dominance in the classroom. Parents were ready to put up with psychological abuse because they thought that talking to someone about it would compromise their child's schooling.